Early Ibadī theology : six kalam texts - Fazārī, ʻAbd Allāh ibn Yazīd, active 767-775. (Islamic History and Civilization, 2014)
Early Ibāḍī Theology presents the critical edition of six Arabic theological texts recently discovered in two manuscripts in Mzāb in Algeria dating from the middle of the 8th century. The texts were sent by their author, the prominent Kūfan Ibāḍī kalām theologian 'Abd Allāh born Yazīd al-Fazārī to North Africa where he had a large following in the Ibāḍī community later known as the Nukkār. They constitute the earliest extant body of Muslim kalām theology and are vital for the study of the initial development of rational theology in Islam. The sophisticated treatment of the divine attributes in these texts indicates that this subject developed considerably earlier in Islamic theology than previously accepted in modern scholarship.